KEARIFAN LOKAL MASYARAKAT DALAM MENGELOLA AREAL BEKAS LADANG BERPINDAH DI DESA SEHE LUSUR KECAMATAN KUALA BEHE KABUPATEN LANDAK The Comunity of Local Wisdom In Managing Used-Areas of Shifting Cultivation In Sehe Lusur Village Sub District of Kuala Beh - na, Uju; Lumangkun, Augustine; Natalina, Uke (Universitas Tanjungpura, 2014)
Research on local wisdom in managing used-areas of shifting cultivation in Sehe Lusur Village, sub district of Kuala Behe District of Landak. The aims to determine the shape of local wisdom in managing used-areas of shifting cultivation and to determine the the influence factors such as: age, knowledge, education, perception, lenght of stay and villagers’ experiences. The samples were using purposive sampling technique. The data were collected through a descriptive method in the form of a survey with interview techniques. Data were analyzed with chi-square. The research showed that in those areas people planted some useful crops and perennials by intercropping. The lands managed traditionally and no special treatment. They rely on soil fertility and work together or mutual cooperation (pengari). The yields are partially self-consumed and sold. There were differences in the frequency rate of local wisdom in managing those areas. The frequencies were tend to moderate. The level of knowledge factor showed a real relationship, education showed a strong relationship; whereas factors of age, perception, length of stay and work experience do not indicate a real relationship with the local wisdom in managing the used-areas of shifting cultivation areas. Keywords: local wisdom, villagers, used-areas of shifting cultivation, forest areas, mix farms